Law and Tradition in Classical Islamic Thought
XIX, 326 p.
Keywords: Bringing together essays on topics related to Islamic law, this book is composed of articles by prominent legal scholars and historians of Islam. They exemplify a critical development in the field of Islamic Studies: the proliferation of methodological approaches that employ a broad variety of sources to analyze social and political developments.